RELIGIUSITAS DAN PSYCHOLOGICAL WELL-BEING - Rahayu, Iin Tri (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2009)
In recent years, social scientists have noted a link between religiosity and many standards of physical and psychological well-being. The possibility that religiosity is linked to health and psychological well-being has attracted attention. Many researches indicate that people who are highly engaged in religious pursuits (e.g. those who frequently attend religious services) or who report that religion is a central aspect of their lives tend to have slightly higher psychological well being, slightly depressive symptoms, and slightly longer lives than their less religious counterparts.